2018
DOI: 10.1002/cphc.201800596
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Crown Ether Macrocycles with Methyl Guanidinium: Insights into the Capture of Charge in Peptides

Abstract: Crown ethers are well known as modulating agents of protein function and interactions. The action of crown ethers is driven by an alteration of the charged moieties of proteins through the capping of cationic amino acid side chains. This study evaluates the conformational features involved in the binding of crown ethers to the side chain of arginine. For this purpose, isolated complexes of methyl guanidinium with 12-crown-4 and 18-crown-6 are characterized with infrared action vibrational spectroscopy and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In fact, in most events of binding of these ions, guanidinium competes favorably with ubiquitous cationic species such as Na + , K + or NH 4 + and protonated amines. These features have served as inspiration for the development of synthetic guanidinium-based molecular materials for sensing and catalysis. Recent studies in our group have corroborated the favorable interactions of guanidinium with carboxylic side groups in a cyclic polyether. In those systems, guanidinium displayed a capability for binding both to the ether and to the carboxylate groups of the host macrocycle. Nevertheless, when guanidinium and protonated amine −NH 3 + groups were both present in the guest cation (as in the free amino acid arginine), guanidinium–carboxylate and ammonium–ether interactions prevailed.…”
Section: Introductionmentioning
confidence: 83%
“…In fact, in most events of binding of these ions, guanidinium competes favorably with ubiquitous cationic species such as Na + , K + or NH 4 + and protonated amines. These features have served as inspiration for the development of synthetic guanidinium-based molecular materials for sensing and catalysis. Recent studies in our group have corroborated the favorable interactions of guanidinium with carboxylic side groups in a cyclic polyether. In those systems, guanidinium displayed a capability for binding both to the ether and to the carboxylate groups of the host macrocycle. Nevertheless, when guanidinium and protonated amine −NH 3 + groups were both present in the guest cation (as in the free amino acid arginine), guanidinium–carboxylate and ammonium–ether interactions prevailed.…”
Section: Introductionmentioning
confidence: 83%
“…1), which are particularly suitable for coordination with the anionic electronic structures of the phosphate, carboxylate and sulfate groups, as well as with neutral polar moieties such as ester and ether groups. [10][11][12][13][14][15][16] This study resumes the efforts of our group on the characterization of guanidinium-phosphate coordination frameworks in isolated complexes. 16 Guanidinium-phosphate interactions have gained particular recognition due to their key role in the control of ATP-mediated phosphorylation reactions and kinase activity, with remarkable implications in the design of novel antitumor agents.…”
Section: Introductionmentioning
confidence: 81%
“…1), which are particularly suitable for coordination with the anionic electronic structures of the phosphate, carboxylate and sulfate groups, as well as with neutral polar moieties such as ester and ether groups. 10–16…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest and most important classes of hosts is crown ethers . Their ability to bind metal cations and small neutral molecules makes them useful for medical applications, chiral recognition, extracting hazardous materials, and more. , Specific symmetric conformers of 18-crown-6 (18C6) with alkali cations were reported as belonging to specific point groups (e.g., C i , C 2 , D 2 , C 3 v , and D 3 d ). In the presence of Li + and Na + , the host is highly folded. ,, Several researchers suggested that non-bonded interactions are the stabilizing factors of alkali cations in crown ethers, , but their effect was not quantified. Both experimental and theoretical studies stress the importance of crown ethers’ flexibility in forming stable complexes. ,,, This flexibility, along with the low barrier for transformation between conformers, poses a significant challenge to the theoretical description of the conformational manifold of these complexes.…”
Section: Introductionmentioning
confidence: 99%
“…10−14 In the presence of Li + and Na + , the host is highly folded. 10,14,15 Several researchers suggested that non-bonded interactions are the stabilizing factors of alkali cations in crown ethers, 16,17 but their effect was not quantified. Both experimental and theoretical studies stress the importance of crown ethers' flexibility in forming stable complexes.…”
Section: ■ Introductionmentioning
confidence: 99%